Sociodemographic aspects, beliefs about lifestyles, and religiosity as predictors of life satisfaction in Peruvian university students: a cross-sectional study - Saintila, Jacksaint; Javier-Aliaga, David; Valle-Chafloque, Ana; Casas-Gálvez, Christian; Barreto-Espinoza, Luz Antonia; Calizaya-Milla, Yaquelin E. (Frontiers in Public Health, 2024)
Introduction Beliefs and practices related to healthy lifestyles and religiosity can play an important role in overall well-being. However, few studies have explored the association between these factors and life satisfaction in the university context. This study examined the association between sociodemographic aspects, lifestyle beliefs, and religiosity with life satisfaction in university students. Methods A cross-sectional predictive study was conducted during the months of March and May 2024 at a private university located in the northern region of Peru. Validated instruments were distributed that included a lifestyle beliefs scale, the Santa Clara Strength of Religious Faith Questionnaire-Short Form (SCSRFQ-SF), the Satisfaction with Life Scale (SWLS) and a sociodemographic data section. A total of 1,258 students participated in the study. Multiple linear regression models were used for predictive analysis. Results Being a student of foreign origin, compared to being Peruvian, is negatively and significantly associated with life satisfaction (β = −0.066, p = 0.003). In contrast, a positive association is observed between belonging to the Faculty of Health Sciences (β = 0.119, p = 0.048) and life satisfaction, compared to students from other faculties. Furthermore, lifestyle beliefs (β = 0.579; p < 0.001) and religiosity (β = 0.182; p < 0.001) are positively and significantly associated with life satisfaction. Conclusion These findings suggest that universities and health professionals should consider promoting healthy lifestyles and supporting religious practices as important strategies to improve student life satisfaction, considering relevant sociodemographic aspects.